PRESENTATION - Reyes de Suárez, Luz Maritza (REDIELUZ, 2023)
One of the challenges of university research is to increase the capacity for internal coordination, adding international linkage capacity, in terms of cooperation and strategic alliances that generate sustainable routes for the benefit of scientific and technological processes in favor of life. What has been proposed represents a common thread that adds relevance and generates trust while integrating human and digital thinking in decision-making. This transforms universities into protagonists and generators of their own horizon, including: ethics in action, generation of trust, quality production, linking knowledge and its social impact. In this context, the digitization of this process and the human condition of research, count the sustainability of life and commits indicators of sharing, for knowledge management through inter-institutional actions.